Try NerdPal! Our new app on iOS and Android

# Find the derivative of $x\sqrt{x^2-1}$

## Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$\frac{\left(x^2-1\right)^{1}+x^2}{\sqrt{x^2-1}}$
Got another answer? Verify it here!

## Step-by-step Solution

Problem to solve:

$\frac{d}{dx}\left(x\sqrt{x^2-1}\right)$

Specify the solving method

1

Apply the product rule for differentiation: $(f\cdot g)'=f'\cdot g+f\cdot g'$, where $f=x$ and $g=\sqrt{x^2-1}$

$\frac{d}{dx}\left(x\right)\sqrt{x^2-1}+x\frac{d}{dx}\left(\sqrt{x^2-1}\right)$

Learn how to solve differential calculus problems step by step online.

$\frac{d}{dx}\left(x\right)\sqrt{x^2-1}+x\frac{d}{dx}\left(\sqrt{x^2-1}\right)$

Learn how to solve differential calculus problems step by step online. Find the derivative of x(x^2-1)^1/2. Apply the product rule for differentiation: (f\cdot g)'=f'\cdot g+f\cdot g', where f=x and g=\sqrt{x^2-1}. The derivative of the linear function is equal to 1. The power rule for differentiation states that if n is a real number and f(x) = x^n, then f'(x) = nx^{n-1}. The derivative of a sum of two or more functions is the sum of the derivatives of each function.

$\frac{\left(x^2-1\right)^{1}+x^2}{\sqrt{x^2-1}}$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$\frac{d}{dx}\left(x\sqrt{x^2-1}\right)$